Economic and Marketing Study of Purse Seine Catch Results in Bone Bay Waters, Bone Regency - Sambolangi, Yerwin Toga; Baso, Aris; Hasani, M. Chasyim (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2023)
Harvesting marine biological resources especially fish, is still largely dotted with fishing activities. One of the fishing businesses engaged in fishing that has already developed in Indonesia, especially in the South Sulawesi Bone Bay is a ring trawl business (Purse seine). The magnitude of the potential of fisheries in the bone bay led to the formation of a large number of purse seine fishing business units in Bone district. However, erratic natural conditions make production yields non-permanent so it is necessary to know how much this business is still feasible to continue. In this purse seine catch production flow, aspects of marketing and distribution anaises are an important part of knowing the effectiveness of production to support the economy of society. The research was conducted from October to November 2020. In this study the income received by the purse seine capture business unit in bone bay was 1,115,964,357.52/year and indicated that the purse seine business carried out by the fishing business actor was feasible to develop by the division between receipts and costs has a value of more than one (>1). Based on the Marketing aspect the value of marketing efficiency of purse seine catches is set according to the marketing channel value <1 which means it can be said that both channels are efficient marketing on each fish commodity.